2006
DOI: 10.2136/sssaj2005.0180
|View full text |Cite
|
Sign up to set email alerts
|

Soil Organic Matter in a West Bengal Inceptisol after 30 Years of Multiple Cropping and Fertilization

Abstract: Rice‐based multiple cropping systems are predominant in the Indo‐Gangetic Plains of Indian subcontinent. A decline in yield of such systems has been observed and ascribed to quantitative and qualitative variations of soil organic matter (SOM). We evaluated the impact of the annual rotation: rice (Oryza sativa L.), wheat (Triticum aestivum L.), jute (Corchorus olitorius L.), with and without fertilizer treatments (control, N, N–P, N–P–K, and N–P–K plus farmyard manure [FYM]) on SOM and aggregate properties. At … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
30
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(48 citation statements)
references
References 37 publications
10
30
6
Order By: Relevance
“…Results from several other long-term Indian experiments also showed similar build up of total SOC due to application of manure with balanced fertilizers (Kanchikerimath and Singh 2001;Rudrappa et al 2005;Mandal et al 2007). Many studies reported that materials with a higher lignin content (FYM) result in a greater accumulation per unit of C input (Manna et al 2006). In contrast to our results, Manna et al (2006) observed decreased total SOC under imbalanced fertilizer application and unfertilized control.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Results from several other long-term Indian experiments also showed similar build up of total SOC due to application of manure with balanced fertilizers (Kanchikerimath and Singh 2001;Rudrappa et al 2005;Mandal et al 2007). Many studies reported that materials with a higher lignin content (FYM) result in a greater accumulation per unit of C input (Manna et al 2006). In contrast to our results, Manna et al (2006) observed decreased total SOC under imbalanced fertilizer application and unfertilized control.…”
Section: Discussioncontrasting
confidence: 99%
“…Many studies reported that materials with a higher lignin content (FYM) result in a greater accumulation per unit of C input (Manna et al 2006). In contrast to our results, Manna et al (2006) observed decreased total SOC under imbalanced fertilizer application and unfertilized control. The gain in SOC concentration in the plots under unfertilized control was probably due to annual C addition from the biomass of both crops (Table 3) and higher humification rate of added SOM.…”
Section: Discussioncontrasting
confidence: 99%
“…This confirms that the method of fertilization helps to maintain or increase the soil organic carbon content under various habitat and agricultural conditions, which is seen from the results of long-term experiments carried out in Poland (Rutkowska et al 2004) and other countries of the world (Manna et al 2006).…”
Section: Resultssupporting
confidence: 63%
“…Compared to no fertilization, some studies suggested that SOC content increases under inorganic fertilization, especially for inorganic nitrogen (N) fertilizers (Majumder et al, 2007;Reid, 2008;Tong et al, 2009;Batlle-Bayer et al, 2010). López-Bellido et al (2010) and Luo et al (2010) suggested that the SOC content does not change, and others suggested that the SOC content decreases (Manna et al, 2006;Khan et al, 2007;Li and Zhang, 2007). Inorganic N fertilizers improve the crop residues in the soil, and thus improve the SOC.…”
Section: Introductionmentioning
confidence: 99%